Introducing Unemployment Insurance to Developing Countries - Milan Vodopivec (Institute for the Study of Labor (IZA), 2009)
The paper identifies key labor market and institutional differences between developed and developing countries, analyzes how these differences affect the working of the standard, OECD-style unemployment insurance (UI) program, and derives a desirable design of unemployment benefit program in developing countries. It argues that these countries faced by large informal sector, weak administrative capacity, large political risk, and environment prone to corruption should tailor the OECD-style UI program to suit their circumstances. To minimize employment disincentives, to ensure affordability, and to minimize administration cots, such adaptations include: (i) relying on self-insurance (via unemployment insurance savings accounts UISAs) as a main source of financing and complementing it by solidarity funding; (ii) simplifying monitoring of job-search behavior and labor market status, and even eliminating personal monitoring of continuing eligibility requirements in the early phases; (iii) keeping modest benefits both in terms of the replacement rate and potential benefit duration; (iv) drawing on employers and workers contributions as sources of financing; and (v) piggybacking on existing networks to administer benefits. Particularly attractive is the UISAs-cum-borrowing version that uses pension wealth as collateral, making the system proof to moral hazard and strategic behavior, and allowing it to be rapidly deployed, such as in response to the currently emerging global economic crises.
Keywords: J65; J68; 330; unemployment; unemployment insurance; unemployment insurance savings accounts; Arbeitslosenversicherung; Einführung; Institutionalismus; Moral Hazard; Ökonomischer Anreiz; Entwicklungsländer